The Use of Vibrotactile Feedback During Dual-Task Standing Balance Conditions in People With Unilateral Vestibular Hypofunction. Issue 5 (June 2018) - Lin, Chia-Cheng; Whitney, Susan L.; Loughlin, Patrick J.; Furman, Joseph M.; Redfern, Mark S.; Sienko, Kathleen H.; Sparto, Patrick J.
Abstract : Hypothesis: People with unilateral vestibular hypofunction (UVH) would have increased postural sway and slower reaction times while using vibrotactile feedback (VTF) during dual-task conditions compared with age-matched controls. Background: VTF has been shown to improve real-time balance performance in persons with vestibular disorders. Future use of this technology outside of the laboratory environment as a real-time balance aid requires that using VTF during dual-tasking scenarios be studied. Method: Nine people with UVH and nine age-matched controls participated in a study focused on assessing the effects of a secondary cognitive task and sensory integration conditions on the root-mean-square of center of pressure (RMS COP) while using VTF. Reaction times from the secondary cognitive task were used to assess the effects of VTF, and sensory integration conditions on the attention required to perform the task. Results: The results showed that there was no group difference between individuals with UVH and age-matched controls on balance performance while using VTF during dual-task conditions. Using VTF significantly degraded the reaction time performance in both groups, and the participants with UVH had slower reaction times compared with controls. Conclusion: People with UVH showed the ability to use VTF to control balance during dual-task conditions, but more attentional resources were needed to perform the secondary cognitive tasks while using VTF.